PI3K Synergizes With Loss of PKC to Elicit Apoptosis via the UPR - Guo, Jinjin (2009)
It is known that Ras mutations, together with loss of PKC, are apoptotic in various types of mammalian cells. The mechanism of how aberrant Ras transmits this apoptotic signaling remains unclear. Using three V12-Ha-ras loop mutants that preferentially bind to and activate one of Ras effectors, we tested the role of Ras downstream pathways in the induction of apoptosis in rat lung epithelia, human lung or prostate cancer cells. After PKC inhibition, the activation of PI3K/Akt renders the susceptibility of cells to apoptosis. We also demonstrate that the amount of ROS is moderately increased in the cells ectopically expressing V12C40 and dramatically elevated by suppression of PKC, which leads to apoptosis through the activation of UPR. Thus, our study suggests that after PKC abrogation, PI3K functions downstream of Ras to perturb the state of cellular redox and signals to ER stress-regulated apoptotic machinery.